Active and regioselective rhodium catalyst supported on reduced graphene oxide for 1-hexene hydroformylation. Issue 4 (30th September 2015) - Tan, Minghui; Yang, Guohui; Wang, Tiejun; Vitidsant, Tharapong; Li, Jie; Wei, Qinhong; Ai, Peipei; Wu, Mingbo; Zheng, Jingtang; Tsubaki, Noritatsu
Abstract : An active and regioselective rhodium catalyst supported on reduced graphene oxide for 1-hexene hydroformylation was prepared by a one-pot liquid-phase reduction method. Abstract : Alkene hydroformylation with syngas (CO + H2 ) to produce aldehydes is one of the most important chemical reactions. However, designing heterogeneous catalysts to realize comparable performance with mature homogeneous catalysts is challenging. In this report, a reduced graphene oxide (RGO) supported rhodium nanoparticle (Rh/RGO) catalyst was successfully prepared via a one-pot liquid-phase reduction method and first applied in 1-hexene hydroformylation. 1-Hexene hydroformylation reaction under different reaction conditions with this Rh/RGO catalyst was investigated in detail. Low reaction temperature and short reaction time effectively enhanced the n / i (normal to iso) ratio of heptanal in the products. The catalytic performance of the Rh/RGO catalyst was also compared with those of Rh supported on other carbon materials, including activated carbon and carbon nanotubes (Rh/AC and Rh/CNTs). The results showed that the Rh/RGO catalyst exhibited the highest 1-hexene conversion and the largest n / i ratio of 4.0 among the tested catalysts. The special 2D nanosheet structure of the Rh/RGO catalyst, rather than the 3D porous and 1D nanotube structures of Rh/AC and Rh/CNTs, respectively, principally contributed to its excellent catalytic performance. These findings disclosed that reduced graphene oxide could be a promising catalyst support for designing heterogeneous hydroformylation catalysts.